2017
DOI: 10.1016/j.aca.2017.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Process modeling and control applied to real-time monitoring of distillation processes by near-infrared spectroscopy

Abstract: A distillation device that acquires continuous and synchronized measurements of temperature, percentage of distilled fraction and NIR spectra has been designed for real-time monitoring of distillation processes. As a process model, synthetic commercial gasoline batches produced in Brazil, which contain mixtures of pure gasoline blended with ethanol have been analyzed. The information provided by this device, i.e., distillation curves and NIR spectra, has served as initial information for the proposal of new st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…By the combination of T 2 and Q control charts, it was possible to detect the in-control tested batch (NOC 13c ) and to distinguish failure batches just from the first minutes of the process. Similarly, de Oliveira et al [30] concluded that the combination of T 2 and Q charts gave specificity and sensitivity results more reliable than their single check when applying MSPC to synthetic commercial gasoline distillation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By the combination of T 2 and Q control charts, it was possible to detect the in-control tested batch (NOC 13c ) and to distinguish failure batches just from the first minutes of the process. Similarly, de Oliveira et al [30] concluded that the combination of T 2 and Q charts gave specificity and sensitivity results more reliable than their single check when applying MSPC to synthetic commercial gasoline distillation.…”
Section: Resultsmentioning
confidence: 99%
“…Before performing MCR analysis, the selection of the proper number of components was performed through singular value decomposition (SVD algorithm on which PCA is based) by the ALS approach. Since two components were used to describe the process changes observed in PCA of mean-centered data, it is consistent that three components were found relevant by ALS applied to the not-centered data, because the rank decreases by one when mean-centering is performed [30].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Mendes and Barbeira 29 performed a study for detecting adulteration and the amount of solvent in gasoline using distillation curves combined with multivariate methods, including PCA and PLS discriminant analysis (PLS‐DA). Oliveira et al 30 designed a distillation‐based quality control procedure to analyze synthetic commercial gasoline, which contains mixtures of pure gasoline blended with ethanol. Their automatic device made it possible to obtain continuous and synchronized measurements of the distillated mass percentage, distillation temperature, and NIR spectra during the distillation process.…”
Section: Introductionmentioning
confidence: 99%
“…The outputs based on spectroscopic measurements come from the use of different multivariate analysis tools, e.g. multivariate calibration models provide prediction of product key properties [6], multivariate curve resolution (MCR) deliver concentration profiles associated with the evolution of compounds in a process [7] and multivariate statistical process control (MSPC) gives indicators that may tell whether the process is on-or off-specifications [8]. In addition to the spectroscopic sensors, most processes are also monitored with simpler devices providing other univariate measurements, such as temperature, pressure, pH or flow rates.…”
Section: Introductionmentioning
confidence: 99%
“…c) Distillation process. This process is monitored by NIR spectroscopy and vapour temperature measurements [7]. Here, the evolution of the distillation process was controlled via data fusion on-line MSPC models based on the combination of compressed NIR-based information, expressed by the concentration profiles derived from multivariate resolution analysis (MCR) of the process spectra and vapour temperature measurements (see Fig.…”
Section: Introductionmentioning
confidence: 99%